2021
DOI: 10.3389/fmolb.2021.745360
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Structural and Minimal Protective Epitope of the Serogroup X Meningococcal Capsular Polysaccharide

Abstract: Despite the considerable progress toward the eradication of meningococcal disease with the introduction of glycoconjugate vaccines, previously unremarkable serogroup X has emerged in recent years, recording several outbreaks throughout the African continent. Different serogroup X polysaccharide-based vaccines have been tested in preclinical trials, establishing the principles for further improvement. To elucidate the antigenic determinants of the MenX capsular polysaccharide, we generated a monoclonal antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Recently, it has been demonstrated that five to six RUs contain the minimal structural and immunogenic epitope of N. meningitidis serogroup X (MenX) capsular polysaccharide. 35 The study at the atomic level of the minimal epitope of group B Streptococcus type III revealed a sialylated epitope spread over two adjacent repeating units. 36 The same methodology applied to N. meningitidis serogroup A identified the O-acetylated trisaccharide as the minimal antigenic epitope.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that five to six RUs contain the minimal structural and immunogenic epitope of N. meningitidis serogroup X (MenX) capsular polysaccharide. 35 The study at the atomic level of the minimal epitope of group B Streptococcus type III revealed a sialylated epitope spread over two adjacent repeating units. 36 The same methodology applied to N. meningitidis serogroup A identified the O-acetylated trisaccharide as the minimal antigenic epitope.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Different conditions (temperature and reaction times) were used depending on the OS MW target. For example, to produce MenX OS with an average of 5 RU, the hydrolysis was performed in 50 mM NaOAc, with a saccharide concentration of 2.5 mg/mL at pH 4.0, 80 °C for ∼18 h, and two times overnight at RT [ 37 ].…”
Section: Methods To Reduce Polysaccharide Sizementioning
confidence: 99%
“…When MenC OS of 2–4, 4–10, and 10–50 kDa, conjugated to P64k by reductive amination following saccharide oxidation, were tested in mice, the IgG antibody levels and bactericidal activity were not statistically different [ 36 ]. With a set of MenX OS of different length (average number of 5, 10 and 20 RU) conjugated to CRM197, the 20 RU OS conjugate induced in mice the optimal response in terms of both anti-MenX antibodies and SBA titers [ 37 ] ( Figure 1 C).…”
Section: Role Of Sugar Length On the Immunogenicity Of Glycoconjugate...mentioning
confidence: 99%
“…Recently, the structural epitope of the MenX CPS was mapped using a Fab derived from a murine bactericidal monoclonal antibody (mAb) obtained against the conjugated MenX PS. 98 Surface Plasmon Resonance (SPR), isothermal titration calorimetry (ITC), and STD-NMR showed binding for a fragment longer than 5 RUs. In silico docking with a hexamer and the structure of the Fab resolved by X-ray crystallography confirmed binding through a network of salt bridges and hydrophobic interactions.…”
Section: Neisseria Meningitidismentioning
confidence: 99%
“…Subsequently a tetramer fragment was generated, and a competitive ELISA showed that the corresponding TT conjugate was a much better competitor than the unconjugated form, indicating the need for longer length CPS fragments to sufficiently emulate the PS epitope. Recently, the structural epitope of the MenX CPS was mapped using a Fab derived from a murine bactericidal monoclonal antibody (mAb) obtained against the conjugated MenX PS . Surface Plasmon Resonance (SPR), isothermal titration calorimetry (ITC), and STD-NMR showed binding for a fragment longer than 5 RUs.…”
Section: Improving Existing Vaccinesmentioning
confidence: 99%